The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1067/mnc.2000.105279
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the automated assessment of left ventricular function with gated perfusion SPECT in the presence of perfusion defects and left ventricular dysfunction: Correlation with equilibrium radionuclide ventriculography and echocardiography

Abstract: Automated gated SPECT provides an accurate assessment of ejection fraction and regional function, even in the presence of an earlier myocardial infarction with large perfusion defects and significant left ventricular dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 20 publications
4
51
1
Order By: Relevance
“…Several groups have compared the quantitative results from the QGS software with similar results from other modalities. Generally in mixed datasets, the concordance with regard to the LVEF is good for contrast ventriculography and ultrasound techniques [6][7][8][9]. Similarly, the concordance with regard to wall thickening is quite good [12].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several groups have compared the quantitative results from the QGS software with similar results from other modalities. Generally in mixed datasets, the concordance with regard to the LVEF is good for contrast ventriculography and ultrasound techniques [6][7][8][9]. Similarly, the concordance with regard to wall thickening is quite good [12].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies report on mean count activity. Chua et al [7] presented a mean count activity of 19.9% ± 10.5 % of maximal myocardial count activity. Hashimoto et al [20] reported that myocardium with a per cent peak count of 40% or less has very low probability of myocardial viability.…”
Section: Prototypesmentioning
confidence: 96%
See 3 more Smart Citations